APPLICATION OF MOTIF BATIK MEGA MENDUNG VISUAL ELEMENTS ON DESIGN OF GLOW IN THE DARK RAIN COAT - Pratiwi Kusumo Dhani (Jurnal Sosioteknologi, 2020)
Motif Batik Mega Mendung comes from the word mega or cloud style has a meaning like a roof that symbolizes the sky as a highly appreciated natural phenomenon in the Trusmi Cirebon area. The result is a traditional batik Trusmi Masina that has a style, motif and character Cirebonan. Cloud shape is a special form found in batik Mega Mendung. In this paper, author apply the visual elements, especially the shape and color of batik motif Mega Mendung on fashion products that are used during the rainy season which is a raincoat, with the application of coloring glow in the dark. Methodology used in this research is experimental quantitative methodology. The experimental method was performed on glow in the dark while the quantitative data was taken by spreading the questionnaire on raincoat users, so it can come up with a design of rain jacket with Mega Mendung motif application which put forward visual element as mentioned by Marvin Bartel.